Information Use Pattern of Researchers in Veterinary Science and Animal Husbandry: a Citation Study - Biswas, Bidhan Chandra; Haque, Md. Enamul (Journal of Information and Knowledge, 2008)
The information use pattern of researchers in veterinary science and animal husbandry was studied by analysing 3888 citations of 26 doctoral dissertations submitted in Bangladesh Agricultural University during the period 1990 to June/2005. This study reveals that researchers under study have primarily depended on periodicals of veterinary science and allied branches for their source of information. The geogrqphical and chronological scattering of citations has also been included. The information inferred in the paper may be of help to Agricultural University Libraries to arrive at a need-based consideration in the selection and acquisition of journals within the limited resources.